2022
DOI: 10.1186/s12891-022-05787-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the effects of ultrasound guided intra-articular injections of platelet-rich plasma (PRP), high molecular weight hyaluronic acid, and their combination in hip osteoarthritis: a randomized clinical trial

Abstract: Background Intra articular (IA) injection of platelet-rich plasma (PRP) and hyaluronic acid (HA) are of the new methods in the management of hip osteoarthritis (OA). The aim of this study was to compare the effectiveness of IA injections of PRP, HA and their combination in patients with hip OA. HA and PRP are two IA interventions that can be used in OA in the preoperative stages. Due to the different mechanisms of action, these two are proposed to have a synergistic effect by combining. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…Out of the seven studies examined, four of them found no incidences of adverse effects or complications in patients who had intra-articular injection treatments with PRP or HA [ 21 , 22 , 24 , 26 ]. In three studies, patients reported experiencing post-injection pain which was consistently higher in the PRP group, of a temporary nature, and resolved on its own [ 20 , 23 , 25 ]. One study noted 10 pain reactions in the PRP group versus six in HA group [ 20 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Out of the seven studies examined, four of them found no incidences of adverse effects or complications in patients who had intra-articular injection treatments with PRP or HA [ 21 , 22 , 24 , 26 ]. In three studies, patients reported experiencing post-injection pain which was consistently higher in the PRP group, of a temporary nature, and resolved on its own [ 20 , 23 , 25 ]. One study noted 10 pain reactions in the PRP group versus six in HA group [ 20 ].…”
Section: Reviewmentioning
confidence: 99%
“…In the second study, PRP participants experienced a significantly higher pain reaction than the HA group [ 23 ]. In the third study, there was a significantly higher incidence of pain during or after injection in the PRP group (3.50±2.22) versus the HA group (3.22±2.40) [ 25 ]. One study documented an isolated occurrence of a superficial hematoma that spontaneously resolved [ 20 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 Some studies have proposed that treating hip OA with combinations of IA injections offers better results. Nouri et al 17 found that composite injection of PRP+HA showed improvement in pain and function sustained for more than six months. However, Dallari et al 15 reported that PRP+HA did not significantly improve pain symptoms at 12 months' follow-up.…”
Section: Introductionmentioning
confidence: 99%